Ecologia populacional, características anatômicas e perfil metabolômico de pilosocereus catingicola (Gürke) Byles & Rowley subsp. salvadorensis (Werderm.) Zappi (Cactaceae). - Barbosa, Alex da Silva (2015)
The cacti are a group of widely distributed plants in semiarid of Paraíba. Your specimens show sensitivity to human disturbance due to low absolute growth rate, restricted range and reliance on dispersal agents, on the other hand appear as important plant genetic resources for the region. Aiming to contribute information to conservation programs, uses and anatomy, the objective of this study was to analyze ecological, anatomical, genetic, and metabolic profile of Pilosocereus catingicola (Gürke) Byles & Rowley subsp. salvadorensis (Werderm.) Zappi from savanna areas of the Paraiba Westland. The assessment was carried out in three contiguous plots caatingas located in the Towns of Arara, Areial and Boa Vista-PB. For ecological study of populations, the soil and climate of populations occurrence was characterized. In each sampled area it was sampled and tagged all individuals by measuring with the aid of calipers DNB and the total height. The populations were described by the density, frequency and absolute dominance, basal area and McGuinness aggregation index. The prediction of spatial configuration for each population was performed with Garmin® Surfer© applications. The anatomical analysis of the cross sections of roots, stems and fruit were freehand obtained, with common razor blade, clarified with sodium hypochlorite (50%), stained with safranin and astra blue and examined by optic microscopy. For the phenology, the stages were analyzed using the activity index (percentage of individuals in the phenology) and an intensity ratio obtained by counting the number of structures produced in each of the stages observed per plant. For the metabolomics analysis, fruits were with different maturity stages of adult specimens with good phenotypic and plant health. The measurement of functional compounds was performed using a spectrophotometer and separation through high performance liquid chromatography in reversed-phase coupled to a mass spectrum. The identifications of metabolites was made on line based on the molecular fragmentation pattern using SciFinder. The three areas soils have a high cation exchange capacity and are eutrophic. Populations have similarity in terms of spatial distribution, yet the anthropization of caatinga areas affects structurally P. catingicola subsp. salvadorensis populations. The Areial specimens have high formation of oxalate crystals in the cells of the cortical root tissue and is distinguished from Arara and Boa Vista, PB populations. Phenological patterns of the population of Boa Vista accompanying rainfall events, heat and to a lesser extent the moisty. The temperature has a positive correlation for all phenophases, with significance at the stage of flower buds. The betacyanins are the alkaloids with the highest expression in the fruit represented in greater quantity by betanin and filocactina. The specimens express more betaxantinas than betacyanins.